Screening for Tuberculosis Infection among Migrants: A Cost-Effectiveness Analysis in the Italian Context - Giulia Russo; Valentina Marchese; Beatrice Formenti; Claudia Cimaglia; Gianluca Di Rosario; Irene Cristini; Paola Magro; Issa El-Hamad; Daniela Maria Cirillo; Enrico Girardi; Alberto Matteelli (MDPI AG, 2023)
Background: Screening of tuberculosis infection (TBI) among migrants from high-incidence countries is a cornerstone of tuberculosis control in low-incidence countries. However, the optimal screening strategy has not been defined yet. Methods: A quasi-experimental study involving migrants residing in the province of Brescia was carried out that aimed at assessing the completion rate, time to completion, preventive treatment initiation rate, and cost-effectiveness of two strategies for TBI screening. They underwent TBI screening with the IGRA-only strategy (arm 1) or with the sequential strategy (tuberculin skin test, TST, followed by IGRA in case of a positive result-arm 2). The two strategies were compared in terms of screening completion, time to complete the screening process, therapy initiation, and cost-effectiveness. Results: Between May 2019 and May 2022, 657 migrants were evaluated, and 599 subjects were included in the study, with 358 assigned to arm 1 and 237 to arm 2. Screening strategy was the only factor associated with screening completion in a multivariable analysis, with the subjects assigned to the IGRA-only strategy more likely to complete the screening cascade (n = 328, 91.6% vs. n = 202, 85.2%, IRR 1.08, 95% CI (1.01-1.14), p = 0.019). The time to complete the screening process was significantly longer for patients assigned to the sequential strategy arm (74 days vs. 46 days, p = 0.002). Therapy initiation did not significantly differ between the two arms, and cost-effectiveness was higher for the sequential strategy. Conclusion: Sequential strategy implementation for TBI screening among migrants may be justified by its higher cost-effectiveness in spite of the lower completion of the screening cascade.